Biomass thermal conversion : pelletisation of lignocelluloses and the effect on the gasification process - Kallis, Kyriakos Xenofon (Cranfield University, 2012)
Agricultural residues and energy crops constitute an important part of the energy chain although they are not being used extensively in the energy generation processes since they are associated with disadvantages such as low bulk and energy densities and handling problems. One solution is the pelletisation of these residues, which solves a great deal of these problems and enables the competition of biomass with other types of fuels. A large amount of work, concerning the combustion of biomass pellets, has been done previously, however, studies on biomass pellet gasification are still limited. An effort is made, in the current project, to connect the pelletisation and the gasification processes so that the work presented here could constitute a guide to the industry. The quality of the pellets to be gasified is affected by the initial pelleting parameters, namely the feedstock moisture content, the feedstock particle size and the die diameter. These parameters in turn, affect the process of gasification. These relationships were studied with the purpose of finding an optimum behaviour in the pelleting process that would allow high efficiencies of pellet gasification. The agricultural residue investigated was oilseed rape due to high cultivation in the UK. Oilseed rape straw (OSRS) was pelletised and used in two types of gasifiers; a downdraft and a spouted fluidised bed gasifier. Other types of biomass pellets such as Miscanthus pellets and Dried Distillers Grains with Solubles (DDGS) pellets were also studied. The gasification performance of the OSRS pellets was compared with the performance during gasification of Miscanthus and DDGS pellets. The results showed that dry and large pellets required more energy to be manufactured than the wet and small pellets. In addition, the results revealed the connection of the initial pelleting parameters and the quality of pellets which was assessed in terms of the pellet density, the bulk density and the pellet durability. The wet pellets with a small particle size had the highest density and the dry pellets had the highest bulk density and durability. The effect of the initial pelleting parameters on the gasification was also studied. It was found that the high feedstock moisture content negatively affected the gasification performance in both downdraft and spouted fluidised bed gasification. The feedstock particle size did not have an effect on the downdraft gasification but a minor effect was identified for the spouted fluidised bed. Large pellets were unable to be processed in the downdraft gasifier due to the increased bed porosity and pellet density and decreased amount of active carbon sites, while both large and small pellets were successfully processed in the spout bed gasifier. The gas higher heating value (HHV) produced in gasification was typically quite low, of between 2-4 MJ/m3. The comparison of the pellets showed that Miscanthus pellets had the highest gasification performance followed by the dry OSRS pellets, the wet OSRS pellets and finally the DDGS pellets. The most important reason for these differences was identified to be the ash content of the pellets.